Theoretical analysis of the energy efficiency policy concept: Japan and Germany’s experience to Kazakhstan (International relations and international law Journal, 2016)
Under the conditions of the current energy crisis, which has already seized all the world, there is much tension around the issue of universal transition to a new level of energy efficiency policy. This policy is of high concern of energy-rich Kazakhstan as it touches on several important and interrelated aspects. The first point is a conscious political decision at the national level, e.g. the way how the state responds to the problem as a whole: whether it carries or delays the adoption of the relevant documents on the basis of the current energy situation and/or on the basis of regional and/or global treaty obligations. In the case when the state is committed to energy-saving philosophy the problem lies beneath the ability to use the least amount of energy while maintaining or increasing the level of consumption. The practice of adaptation of the new energy policy theoretical approaches in Japan is highly attractive as a possible background to the energy policy of Kazakhstan.
Keywords: energy efficiency; theoretical approaches; public policy; Germany; Japan; Conservation Act; Kazakhstan